Research on Procrastination During Exams, Mental Health Care, ADHD and its Preventions (London Journal of Medical and Health Research, 2025)
When students put off preparing for an exam despite knowing they have a deadline and should do so, this is known as procrastination by examination. Students who are anxious about failing the test may put things off. They may put off doing it if they are having trouble understanding the topic. Students who have bad study habits may put off tasks. Depression, anxiety, low self-esteem, and ADHD (Attention Deficit Hyperactivity Disorder) have all been related to procrastination. A neurological condition known as ADHD can impact both adults and children. Hyperactive tendencies, difficulty focusing on activities, and an inability to regulate impulses are all possible symptoms of ADHD2. The disease does, however, also have several advantages and strengths. The primary aim of this study in the exam environment is the integration of procrastination findings by examination. The findings can be used to promote improvements in exam scores, writing techniques, academic performance indicators, and the entire exam and learning experience for students. We also expect that our work will encourage more research using materials connected to tests and other texts to help candidates avail themselves of excellent exam-related activities, which are essential to avoiding and are required to receive higher scores on their exams. The investigators chose the ICSE board schools in the sub-urban areas of Mumbai. In 2024, the researchers distributed 1400 questionnaires to the 12 ICSE Board Schools. 624 students, 227 teachers, 228 parents, and 232 guardians from these participating schools93.64% of respondents were answered. The research reflects that every government must take care of the students and provide effective counseling centres through national, and state representatives it will be required in these digital environments to take care of the future generation because based on necessity everyone procrastinates using mobile phones for their related studies. The usage of mobile also caused procrastination from elementary to research.
Keywords: macular hole; microinvasive vitrectomy; platelet-rich plasma; internal limiting membrane; Artery of Percheron; thalamic infarct; bilateral stroke; young adult; vertical gaze palsy; altered consciousness; cephalic screw; intrapelvic migration; hip fracture; Gamma 3 nail; PFNA nail; surgery complications.; ASD; Triple X Trisomy; Early Diagnosis; cost; communication; mind; Homo Sapiens; Species. Violence; Microbiome; Immune System; Suffering; prevention; Procrastination; Examination; Mental health care; Attention Deficit Hyperactivity Disorder ADHD; Action Control; Intention; Mental and Physical Stress. ICSE.